Scrutinizing Immutability: Research on Sexual Orientation and U.S. Legal Advocacy for Sexual Minorities. Issue 4 (3rd May 2016) - Diamond, Lisa M.; Rosky, Clifford J.
Abstract : We review scientific research and legal authorities to argue that the immutability of sexual orientation should no longer be invoked as a foundation for the rights of individuals with same-sex attractions and relationships (i.e., sexual minorities). On the basis of scientific research as well as U.S. legal rulings regarding lesbian, gay, and bisexual (LGB) rights, we make three claims: First, arguments based on the immutability of sexual orientation are unscientific, given what we now know from longitudinal, population-based studies of naturally occurring changes in the same-sex attractions of some individuals over time. Second, arguments based on the immutability of sexual orientation are unnecessary, in light of U.S. legal decisions in which courts have used grounds other than immutability to protect the rights of sexual minorities. Third, arguments about the immutability of sexual orientation are unjust, because they imply that same-sex attractions are inferior to other-sex attractions, and because they privilege sexual minorities who experience their sexuality as fixed over those who experience their sexuality as fluid. We conclude that the legal rights of individuals with same-sex attractions and relationships should not be framed as if they depend on a certain pattern of scientific findings regarding sexual orientation.